Application of integrated service mode of Traditional Chinese Medicine and health care in "One Syndrome and One product" ward (中医医护一体化服务模式在"一证一品"专科病房中的应用) - ZHANG Yuan (张媛); MA Hongxia (马洪霞); GUO Ning (郭宁); KANG Jingfan (康静璠); Zhu Chunzi (竺春子) (Association of Integrative Nursing, 2021)
In the form of a medical team, integrated service model of Traditional Chinese Medicine and medical care is designed to provide overall health care service consisting of treatment, nursing and rehabilitation. The implementation of the integrated service model in the "One Syndrome and One product" specialist ward has enabled patients to receive more high-quality and safe care, improved patient satisfaction, and at the same time improved the efficiency of medical care and effectively promoted the construction of "One Syndrome and One product" nursing. ("中医医护一体化"服务模式是以医护小组的形式为患者提供治疗、护理、康复一体化的责任制整体医疗服务, 旨在为患者提供更加高质、安全的护理, 促进"一证一品"专科病房的建设。)